Zirconium-Based Metal–Organic Framework Mixed-Matrix Membranes as Analytical Devices for the Trace Analysis of Complex Cosmetic Samples in the Assessment of Their Personal Care Product Content - Gutiérrez-Serpa, Adrián; Kundu, Tanay; Pasán, Jorge; Jiménez-Abizanda, Ana I.; Kaskel, Stefan; Senkovska, Irena; Pino, Verónica (ACS Applied Materials and Interfaces, 2022)
A device comprising a zirconium-based metal–organic framework (MOF) mixed-matrix membrane (MMM) framed in a plastic holder has been used to monitor the content of personal care products (PCPs) in cosmetic samples. Seven different devices containing the porous frameworks UiO-66, UiO-66-COOH, UiO-67, DUT-52, DUT-67, MOF-801, and MOF-808 in polyvinylidene fluoride (PVDF) membranes were studied. Optimized membranes reach high adsorption capacities of PCPs, up to 12.5 mg·g–1 benzophenone in a 3.0 mg·L–1 sample. The MMM adsorption kinetics, uptake measurements, and isotherm studies were carried out with aqueous standard solutions of PCPs to ensure complete characterization of the performance. The studies demonstrate the high applicability and selectivity of the composites prepared, highlighting the performance of PVDF/DUT-52 MMM that poses uptakes up to 78% for those PCPs with higher affinity while observing detection limits for the entire method down to 0.03 μg·L–1. The PVDF/DUT-52 device allowed the detection of parabens and benzophenones in the samples, with PCPs found at concentrations of 1.9–24 mg·L–1
CRIS-Team Scopus Importer:2022-04-14
Keywords: environmental analyses; isotherms; metal−organic frameworks; mixed-matrix membranes; personal care products; polymeric composite